Impact of metabolic-associated fatty liver disease on the cholesterol efflux capacity of high-density lipoproteins in adolescents with type 2 diabetes - Orozco Morales, José Antonio; Medina Urrutia, Aída Xochitl; Tamayo, Margarita Torres; Reyes Barrera, Juan; Galarza, Esteban Jorge; Juárez Rojas, Juan Gabriel; Dies Suarez, Pilar; Méndez Sánchez, Nahum; Díaz Orozco, Luis Enrique; Velázquez-López, Lubia; Medina Bravo, Patricia (Frontiers in Pediatrics, 2024)
Context: Type 2 diabetes (DM2) is an emerging disease in the pediatric population. DM2 is associated with metabolic-associated fatty liver disease (MAFLD). High-density lipoproteins (HDLs) are lipoproteins that are believed to have atheroprotective properties that reduce the risk of cardiovascular disease (CVD). Current evidence suggests that the physicochemical and functional features of HDLs may play a key role in the pathogenesis of atherosclerosis.Objective: We aimed to assess the impact of MAFLD on cholesterol efflux capacity (CEC) in adolescents with DM2.